Dřevěná nosná konstrukce rodinného domu - Perhalová, Anna (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Předmětem této bakalářské práce je návrh a statické posouzení dřevěné nosné konstrukce rodinného domu. Objekt je situován do Slavkova u Brna. Návrh střešní konstrukce vychází z architektonické studie prof. Ing. arch. Ivana Rullera. Půdorysné rozměry nosné konstrukce jsou 11,63x15,00m a výška hřebene střechy je 6,56m. Střešní konstrukce je vytvořena jako systém krokví, který je podepřen příhradovým nosníkem, průvlakem a pozednicemi. Horizontální síly jsou přeneseny do stěnových panelů táhly, jenž jsou ukotvena do pozednic.

The subject of this bachelor's thesis is design and static assessment of timber load bearing structure of the family house. The object is located in Slavkov u Brna. Design of truss structure is based on architectural study by prof. Ing. arch. Ivan Ruller. The ground plan dimensions of load bearing structure are 11,63x15,00 meters and the height of the roof ridge is 6,56 meters. The structure of the roof is made as a rafter system, which is supported on the lattice truss, on the main beam and wall rafters. Horizontal forces are transferred into the wall panels by means of tight members, which are anchored to wall rafters.
Timber load bearing structure of a family house
Keywords: Střešní konstrukce; stěnová konstrukce; krokev; příhradový nosník; průvlak; pozednice; táhlo; panel; Roof structure; wall structure; rafter; truss beam; main beam; wall rafter; tight member; wall panel